The Influence Of Positive Emotions On Hypertension Relapse: A Cross-Sectional Study - Yunita, Rizka; Hartono, Dodik (Universitas Tribhuwana Tunggadewi, 2025)
Hypertension has become one of the leading causes of death due to its potential to cause systemic complications. Individuals diagnosed with hypertension must undergo regular treatment and medication because they have a high risk of recurrence. One of the factors influencing this is intrinsic factors such as positive emotions. The purpose of this study is to analyze positive emotions in recurrence symptoms in hypertensive. The study design employed a correlational analysis with a cross-sectional approach. The study population consisted of 98 hypertensive in Karangbong Village, Pajarakan, Probolinggo. The sample size was 79 individuals who met the inclusion and exclusion criteria. The sampling technique used was purposive sampling. Inclusion criteria included patients with hypertension for more than 3 years, with a history of hypertension with systolic blood pressure ? 120 mmHg and diastolic blood pressure ? 80 mmHg. Exclusion criteria included patients with hypertension who had visual and hearing impairments, and complications such as diabetes mellitus, heart disease, and stroke. The positive emotion instrument used the Dispositional Positive Emotions Scale (DPES) questionnaire and the hypertension recurrence symptom questionnaire. Data analysis used the Spearman rank test. The findings of the study indicated that most respondents had positive emotions (68%) and hypertension recurrence symptoms (66%). There was a significant correlation between positive emotions and recurrence symptoms in hypertensive patients with a p value of 0.001. Hypertensive patients are prone to recurrence symptoms due to low positive emotions. Respondents are encouraged to manage their emotions to prevent the onset of hypertension recurrence symptoms. Future research is recommended to incorporate psychotherapeutic interventions, such as peer support groups, to further explore their potential impact on the outcomes.